Empagliflozin attenuates arrhythmogenesis via inhibition of O-GlcNAcylation in diastolic phase of diabetic cardiomyopathy. (3rd October 2022) - Kadosaka, T; Watanabe, M; Natsui, H; Koizumi, T; Koya, T; Nakao, M; Hagiwara, H; Kamada, R; Temma, T; Anzai, T
Abstract: Background: Diabetic cardiomyopathy is an important complication of diabetes mellitus (DM) and reported to increase the risk of fatal ventricular arrhythmias. Recent clinical trials showed that empagliflozin (EMPA), a selective sodium-glucose co-transporter 2 (SGLT2) inhibitor, improved cardiovascular outcomes regardless of the presence of diabetes and the traditional cardiovascular risk factors. Despite the promising benefit of EMPA on heart failure treatment, its beneficial effect in the context of anti-arrhythmic therapy has not been fully examined. We therefore aimed to examine anti-arrhythmic effect of acute EMPA treatment especially onto calcium (Ca2+) handling in diabetic cardiomyocytes. Methods: We assessed echocardiography, hemodynamic study, electrophysiology, Ca2+ handling and protein expression in C57BLKS/J-leprdb/db mice (db/db mice), a leptin receptor-deficient model of obesity and Type 2 diabetes, and their non-diabetic lean heterozygous Leprdb/+ littermates (db/+ mice). Results: The 16-week-old db/db mice had preserved systolic function but exhibited diastolic dysfunction. In arrhythmia induction using ex-vivo Langendorff-perfused hearts, db/db mice showed a significantly increased premature ventricular complex (PVC) by 2x Ca2+ and 1μM isoproterenol load than control, which was attenuated by EMPA perfusion (1 μM). Diabetic cardiomyocytes showed an increased frequency of spontaneous Ca2+ sparks and waves, and decreased Ca2+ transient amplitude and sarcoplasmic reticulum (SR) Ca2+ content. Ca2+ transient decay tau and time to 50% decay were significantly prolonged in diabetic cardiomyocytes. These data indicating the impaired Ca2+ handling in diabetic cardiomyocytes were normalized by acute administration of EMPA (1 μM), while the administration of NHE inhibitor (Cariporide 10 μM) did not show significant differences. In the protein expression analysis, CaMKII Thr287 autophosphorylation and CaMKII-dependent RyR2 S2814 phosphorylation were significantly increased in diabetic hearts, which were inhibited by short-term (30 min) perfusion of EMPA (1 μM). The expressions of SERCA2a and phospholamban were not significantly different among three groups. Lastly, whole hearts O-GlcNAcylation, one of the important post translational modifications, was significantly reduced by EMPA treatment. Conclusion: EMPA improved intracellular Ca2+ handling and attenuated arrhythmogenesis in mice with diabetic cardiomyopathy at the diastolic dysfunction phase, suggesting that EMPA may exhibit this anti-arrhythmic effect by normalization of intracellular calcium handling via inhibiting O-GlcNAcylation. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Boehringer Ingelheim